IDENTIFYING BIOCHEMICAL CHANGES IN THE BLOOD DURING COLIC IN HORSES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Currently, equestrian sports are rapidly developing in our country, and attention to this field is growing. This, in turn, requires high-quality veterinary services for valuable horses and those with high genetic potential. There are many problems hindering the development of horse breeding in our country, the main ones being infectious and non-infectious diseases of horses. This article discusses colic — one of the most common diseases among horses, which, if not treated in time, can lead to death. Colic is very widespread among horses and causes serious damage to horse-breeding farms. Therefore, in this research, we have aimed to shed light on the diagnosis, treatment, and prevention of colic in line with practical needs.